Formalin safety in pathology laboratory and innovative monitoring for airborne formaldehyde exposure - Dugheri, Stefano (Array, 2021)
This review is directed at preventive health professionals, anatomic pathologists and technicians to focus their attention on the rapidly growing field of safe formalin practices. An updated overview of the most recent improvements in preventive measures versus formaldehyde (FA) in the anatomic pathology laboratories (APL) is provided. The occupational hygienist role and the required knowledge for a modern and clear occupational exposure assessment are described. Real-time, in-continuous, commercial analyzers for repeated FA exposure assessment are considered to evaluate technical changes in air monitoring programs, introduced to mitigate FA emissions, in compliance with the adopted limit values. To better choose the adequate instrumentation, the main features of each FA monitoring instrument recently introduced on the market are listed. Moreover, the main features of the modern workflow setting in APL are summarized. A computer-based scientific and non-scientific reports search by key-words was performed on PubMed, Web of Science, Google Scholar and Google Patents databases, querying the following topics: i) grossing workstation for ergonomic layout, ii) commercially available direct reading tools to measure formalin, iii) real-time, in-continuous FA monitoring instruments for sale. This review represents a useful tool to summarize the technical requirements and expert know-how necessary to minimize FA emissions and produce an exhaustive FA assessment in the APL.